The Encoding / Decoding Model on Keats’s “Ode on a Grecian Urn” as a Thing - Hussein Salimian Rizi; Pyeaam Abbasi (K@ta: A Biannual Publication on the Study of Language and Literature, 2016)
John Keats, a main figure in the second generation of Romantic poets, was not generally well received by his contemporary critics, though during the course of time, he has become one of the most beloved poets. Stuart Hall proposes an analytical model of communication, namely the encoding / decoding model, which assumes a complex structure of relations to be produced and sustained through linked but distinctive moments which are termed as production, circulation, distribution/ consumption, and reproduction. This paper employs Hall’s encoding / decoding communication model as a yardstick to move beyond his approach, which mainly addresses modern mass media and communication system, and relate the distinctive moments playing integrally in encoding and decoding to Keats’s Ode on a Grecian Urn (1819). Furthermore, there is an attempt to turn the spotlight on the ode’s durability after the French Revolution passions abate and the poem starts to gain its thingness.